1975
DOI: 10.1364/ao.14.002639
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance and durability of Ag mirrors coated with thin layers of Al_2O_3 plus reactively deposited silicon oxide

Abstract: A technique for producing adherent and well-protected front surface Ag mirrors with an evaporated Al(2)O(3) + SiO(x) overcoat and an evaporated Al(2)O(3) underlayer is described. A thin Al(2)O(3) layer promotes adhesion between the Ag film and its substrate. The optimum thickness of each outer layer necessary to give good adhesion and protection to the Ag surface with minimal loss in reflectance due to ir absorption was found to be about 300 A for the Al(2)O(3) layer and between 1000 A and 2000 A for the SiO(x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The interactions between silver and sulfur have been recognized since antiquity and are technologically relevant for preservation, chemistry, medicine, and engineering applications. Acanthite tarnish gradually accumulates on evaporated silver metal at an approximate rate of about half a nanometer per day . Bennet found that the reaction is fastest on rough surfaces devoid of Ag 2 S and observed a tendency for silver sulfide to deposit in clumps, rather than in a continuous passivating film .…”
Section: Progression Of the Tarnishing Reactionmentioning
confidence: 99%
“…The interactions between silver and sulfur have been recognized since antiquity and are technologically relevant for preservation, chemistry, medicine, and engineering applications. Acanthite tarnish gradually accumulates on evaporated silver metal at an approximate rate of about half a nanometer per day . Bennet found that the reaction is fastest on rough surfaces devoid of Ag 2 S and observed a tendency for silver sulfide to deposit in clumps, rather than in a continuous passivating film .…”
Section: Progression Of the Tarnishing Reactionmentioning
confidence: 99%
“…Normally, one would overcoat the silver with a transparent dielectric to protect it against attack by atmospheric or atomic oxygen. An overcoat can change the reflectivity if deposited in thick enough layers [7]. For simplicity, we will use the optical properties of uncoated silver.…”
Section: A Collectormentioning
confidence: 99%
“…Protective oxide overcoats 2,7,[14][15][16][17][18][19][20][21][22] usually have absorption bands in the thermal infrared that can dramatically increase emissivity, exhibit significant losses at high angles of incidence, show transmission dips near 3µ due to water adsorption, and impose significantly increased complexity and cost on the deposition system. Reflectance, scattering, adhesion, and durability of evaporated Al films are a function of several interdependent deposition parameters listed below in order of importance:…”
Section: Coating Objectivesmentioning
confidence: 99%